2021
DOI: 10.1016/j.xnsj.2020.100048
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-impregnated calcium sulfate beads compared with vancomycin powder in adult spinal deformity patients undergoing thoracolumbar fusion

Abstract: Introduction Adult spinal deformity (ASD) surgery patients are at higher risk for surgical site infections (SSIs) due to large incisions, high blood loss, long surgical duration, and extensive instrumentation. The use of vancomycin powder has demonstrated inconsistent results in ASD surgery. Antibiotic-impregnated calcium sulfate beads have been used in arthroplasty and foot and ankle surgery with promising results. The purpose of this study was to provide preliminary data on the use of vancomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…W ithin elective spine surgery, surgical site infections (SSIs) contribute significant morbidity and additional cost. 1,2 Multiple mechanisms have been proposed for prevention of SSIs including the use of intrawound vancomycin, 3 adjustment of perioperative antibiotics, or preoperative optimization and testing. [4][5][6] Among these, preoperative testing and decolonization for methicillinresistant Staphylococcus aureus (MRSA) is an attractive option because of promising results seen in other orthopedic subspecialties such as hip and knee arthroplasty, and several large studies have shown significant reduction in infection rates after implementation of screening and decolonization programs.…”
mentioning
confidence: 99%
“…W ithin elective spine surgery, surgical site infections (SSIs) contribute significant morbidity and additional cost. 1,2 Multiple mechanisms have been proposed for prevention of SSIs including the use of intrawound vancomycin, 3 adjustment of perioperative antibiotics, or preoperative optimization and testing. [4][5][6] Among these, preoperative testing and decolonization for methicillinresistant Staphylococcus aureus (MRSA) is an attractive option because of promising results seen in other orthopedic subspecialties such as hip and knee arthroplasty, and several large studies have shown significant reduction in infection rates after implementation of screening and decolonization programs.…”
mentioning
confidence: 99%
“…There have been many articles on the topical of local vancomycin to reduce the risk of infection after orthopaedic surgery [3,38,39]. Moreover, vancomycin impregnated bone graft has been also widely used in spinal surgery [40][41][42]. Therefore, a prospective randomized study with an adequate patient number is needed to clarify the benefits of vancomycin impregnated autogenous bone graft and bone substitute on preventing DSSI following degenerative lumbar spine fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Localized administration of antibiotics can be advantageous due to the ability to achieve a higher drug concentration at the infected site while limiting systemic toxicity as well as avoiding unwanted metabolic and pharmacokinetic effects that can reduce the efficacy of drug delivery. The localized delivery of antibiotic-loaded calcium sulphate beads has been investigated as a treatment option or prophylaxis for numerous orthopaedic disorders, such as periprosthetic joint infections, adult spinal deformity patients undergoing thoracolumbar fusion, adult chronic osteomyelitis, localized calcaneal osteomyelitis and diabetic foot osteomyelitis [4][5][6][7][8]. However, no studies exist in literature on the use of localized antibiotic delivery to treat AHOM in children.…”
Section: Introductionmentioning
confidence: 99%